2017
DOI: 10.3389/fpls.2017.00668
|View full text |Cite
|
Sign up to set email alerts
|

Stable Internal Reference Genes for Normalizing Real-Time Quantitative PCR in Baphicacanthus cusia under Hormonal Stimuli and UV Irradiation, and in Different Plant Organs

Abstract: Baphicacanthus cusia (Nees) Bremek, the plant source for many kinds of drugs in traditional Chinese medicine, is widely distributed in South China, especially in Fujian. Recent studies about B. cusia mainly focus on its chemical composition and pharmacological effects, but further analysis of the plant's gene functions and expression is required to better understand the synthesis of its effective compounds. Real-time quantitative polymerase chain reaction (RT-qPCR) is a powerful method for gene expression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
1
16
1
Order By: Relevance
“…18S is a frequently used HKG and is widely used for normalization in qRT-PCR analysis. Wang et al (2017) reported that 18S rRNA was one of the most stably expressed gene under diverse heavy metals stresses in tea plants; Huang et al (2017) also found that 18S rRNA was the most stable gene under UV irradiation and hormonal stimuli in Baphicacanthus cusia . However, our analysis results suggested that 18S was the most unstable RG in all of the experiment groups because of its excessively high expression level.…”
Section: Discussionmentioning
confidence: 97%
“…18S is a frequently used HKG and is widely used for normalization in qRT-PCR analysis. Wang et al (2017) reported that 18S rRNA was one of the most stably expressed gene under diverse heavy metals stresses in tea plants; Huang et al (2017) also found that 18S rRNA was the most stable gene under UV irradiation and hormonal stimuli in Baphicacanthus cusia . However, our analysis results suggested that 18S was the most unstable RG in all of the experiment groups because of its excessively high expression level.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, BcEPSPS in B. cusia is sensitive to glyphosate, which indicates that the BcEPSPS protein is a class I protein. As several glyphosate-resistant mutants of class I EPSPS have been identified, and most of the class I EPSPS mutants display increased glyphosate resistance [21], it is useful to create a glyphosate-resistant mutant of a B. cusia EPSPS using a directed evolution strategy [22].…”
Section: Discussionmentioning
confidence: 99%
“…18S rRNA is sometimes utilized for expression normalization in angiosperms [ 70 , 71 ], but there are also numerous reports about its expression instability [ 13 , 14 ]. 18S rRNA exhibited variable transcript levels in S .…”
Section: Discussionmentioning
confidence: 99%